Assessment of dry residual biomass potential for use as alternative energy source in the party of General Pueyrredon, Argentina - Roberts, Justo Jose [UNESP]; Cassula, Agnelo Marotta [UNESP]; Prado, Pedro Osvaldo; Dias, Rubens Alves [UNESP]; Perrella Balestieri, Jose Antonio [UNESP] (Elsevier B.V., 2015)
The present article assesses the residual biomass availability and its energy potential in the Party of General Pueyrredon, a region located southeast of the province of Buenos Aires, Argentina. These were considered herbaceous and vegetable residues derived from the agricultural activity developed in the region, and forest residues resulting from the pruning of urban trees and garden maintenance. The estimates were based on statistical information of the 2011-2012 harvest and a series of parameters obtained from an extensive literature review. The calculations resulted in an availability of residual biomass of 204,536 t/year, implying an energy potential of 2605 TJ/year. If this biomass is used to generate electricity, it could supply 76,000 users from Mar del Plata city, the largest consumer center in the region. If the same available biomass is used for heat generation, 25,160 users could be supplied by the available residual biomass. The authors concluded that the residual biomass energy potential is significant in the studied region, but a more detailed study must be conducted to assess the techno-economic feasibility of using the available residual biomass as alternative energy source. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Renewable energy; Residual biomass; Energy potential; Electricity generation; Heat generation